2021
DOI: 10.1038/s41398-021-01603-4
|View full text |Cite
|
Sign up to set email alerts
|

Psilocin, LSD, mescaline, and DOB all induce broadband desynchronization of EEG and disconnection in rats with robust translational validity

Abstract: Serotonergic psychedelics are recently gaining a lot of attention as a potential treatment of several neuropsychiatric disorders. Broadband desynchronization of EEG activity and disconnection in humans have been repeatedly shown; however, translational data from animals are completely lacking. Therefore, the main aim of our study was to assess the effects of tryptamine and phenethylamine psychedelics (psilocin 4 mg/kg, LSD 0.2 mg/kg, mescaline 100 mg/kg, and DOB 5 mg/kg) on EEG in freely moving rats. A system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 79 publications
(131 reference statements)
2
16
0
Order By: Relevance
“…The changes in resting state EEG, which included decreased spectral power in the alpha/beta bands, accompanied by widespread increases in signal diversity, were not specific to the visual system, but also correlated with somatic and metacognitive/affective domains (343,344). Interestingly, a recent EEG study in freely moving rats showed some overlap with human studies, with a time-dependent global decrease and desynchronization of EEG activity, particularly in the frontal and sensorimotor cortex (345). Similar to the previously discussed vulnerability to adverse effects of psychedelics in people with incoherent self-concept/aberrant salience in the context of psychosis spectrum disorder, baseline dysfunction in the some of the perceptual systems may increase the risk of adverse events in psychedelic therapy.…”
Section: Language and Perceptionmentioning
confidence: 98%
“…The changes in resting state EEG, which included decreased spectral power in the alpha/beta bands, accompanied by widespread increases in signal diversity, were not specific to the visual system, but also correlated with somatic and metacognitive/affective domains (343,344). Interestingly, a recent EEG study in freely moving rats showed some overlap with human studies, with a time-dependent global decrease and desynchronization of EEG activity, particularly in the frontal and sensorimotor cortex (345). Similar to the previously discussed vulnerability to adverse effects of psychedelics in people with incoherent self-concept/aberrant salience in the context of psychosis spectrum disorder, baseline dysfunction in the some of the perceptual systems may increase the risk of adverse events in psychedelic therapy.…”
Section: Language and Perceptionmentioning
confidence: 98%
“…Previous studies in animal models demonstrated that 5-HT2A and 5-HT1A receptors finely tune the amplitude of gamma oscillations [ 57 ], and serotonin-boosting medications suppress gamma activity [ 58 , 59 ], possibly through 5-HT1AR [ 57 ]. Our recent study [ 14 ] showed the global desynchronization of gamma activity by tryptamines (such as psilocin) administered to rats. Thus, we expected that psilocybin would attenuate the gamma response in a similar manner, as seen in various states with disrupted E/I balance and cognition, including psychosis or during intoxication with other psychedelic substances, such as ketamine [ 25 , 26 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Psilocybin has been shown to negatively affect the electrophysiological markers of both early visual (P1 and N170)/auditory (N100) [ 9 , 10 , 11 , 12 ] and higher-order attentive cognitive processing (P300) [ 9 , 13 ], but the mismatch negativity (MMN), as a marker of pre-attentive cognition [ 9 , 12 ], was not attenuated. Similarly, serotoninergic psychedelics, including psilocin, the active metabolite of psilocybin, have been shown recently to decrease gamma oscillations in the animal model [ 14 ]. Although gamma activity is one of the most valuable avenues for understanding the neurobiology of cognitive processing [ 15 ], the resting state gamma oscillations are difficult to study using EEG in humans due to contamination with muscle artefacts.…”
Section: Introductionmentioning
confidence: 99%
“…When looking at these electrophysiological changes in the brain, research groups have found that this drug administration causes broadband desynchronization and a disconnect in neurons in the sensorimotor cortex on EEG monitoring [ 16 ]. The results are an overall resetting due to decreased global activity and connectivity.…”
Section: Alternative Medicationsmentioning
confidence: 99%